The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0189982
|View full text |Cite
|
Sign up to set email alerts
|

The gene encoding the insulin-like androgenic gland hormone in an all-female parthenogenetic crayfish

Abstract: Male sexual differentiation in crustaceans is controlled by the androgenic gland (AG), a unique male endocrine organ that, in decapods, is located at the base of the 5th pereiopod. In these animals, the insulin-like androgenic gland hormone (IAG) is the major factor secreted from the AG to induce masculinization and maintain male characteristics. It has, however, recently been proposed that this hormone also plays a role in growth and ovarian development in females. In this study, we tested such a possibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 30 publications
(50 reference statements)
1
27
0
Order By: Relevance
“…Similar findings have been reported previously (e.g. Chung, 2014;Huang et al, 2014;Levy et al, 2017;Shi et al, 2019).…”
Section: Expressionsupporting
confidence: 92%
“…Similar findings have been reported previously (e.g. Chung, 2014;Huang et al, 2014;Levy et al, 2017;Shi et al, 2019).…”
Section: Expressionsupporting
confidence: 92%
“…The deduced sequence of the EsIAG pre‐peptide contains a signal peptide on N terminus (19 aa), A chain (44 aa), B chain (31 aa), and C peptide (57 aa). The A and B chains were separated by the putative cleavage sites RRTR and RFRR in C peptide (Levy, Rosen, Simons, Savaya Alkalay, & Sagi, ). In addition, N‐linked glycosylated site (NCT) (Aizen et al, ; Ventura, Fitzgibbon, Battaglene, Sagi, & Elizur, ) in the A chain was also found in the deduced EsIAG.…”
Section: Resultsmentioning
confidence: 99%
“…To date, full‐length homologous IAG cDNA have been cloned in many commercially important decapod crustaceans, including crabs (Chung, Manor, & Sagi, ; Huang et al, ; Lawrence et al, ), crayfish (Levy et al, ; Manor et al, ; Rosen et al, ), prawns (Banzai et al, ; Ma et al, ; Phoungpetchara et al, ), and other shrimps (Li, Li, Sun, & Xiang, ; Vazquez‐Islas, Garza‐Torres, Guerrero‐Tortolero, & Campos‐Ramos, ; Zhang, Sun, & Liu, ). However, multiple sequence alignment showed that these IAG shared low similarities among different genus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations